The prognostic role of Gender‐Age‐Physiology system in idiopathic pulmonary fibrosis patients treated with pirfenidone. (6th March 2019) - Harari, Sergio; Caminati, Antonella; Confalonieri, Marco; Poletti, Venerino; Vancheri, Carlo; Pesci, Alberto; Rogliani, Paola; Luppi, Fabrizio; Agostini, Carlo; Rottoli, Paola; Sanduzzi Zamparelli, Alessandro; Sebastiani, Alfredo; et al.
Abstract: Introduction: Gender, age, physiology (GAP) system have proven to be an easy tool for predicting disease stages and survival in idiopathic pulmonary fibrosis (IPF) patients. Objective: To validate mortality risk as determined by the GAP system in a real‐life multicentre IPF population treated with pirfenidone. Methods: The study included patients who received pirfenidone for at least 6 months. The GAP calculator and the GAP index were determined. The primary outcome was all‐cause mortality. The prognostic accuracy of the GAP system was evaluated with respect to calibration and discrimination. Results and Conclusion: Sixty‐eight IPF patients were enrolled in the study. The median follow‐up was 2.4 years (range 0.1‐7.4 years). A total of 22 deaths as first event (32%) and of 10 lung transplantation (15%) were recorded. The cumulative incidence of mortality at 1, 2 and 3 years was 10.4%, 22.4% and 38.4%, respectively. The differences between the predicted and observed mortality were not significant for the GAP index while the observed mortality become comparable to that predicted by the GAP calculator only in the third year of follow‐up. The C‐index for the GAP index was 0.74 (95% CI 0.57‐0.93) while the C‐statistic value for the GAP calculator was 0.77 (95% CI 0.59‐0.95).